Perbedaan Model Take and Give dan Problem Solving terhadap Pemahaman Konsep IPA Kelas IV SDN Bojongrenged 1 - Puspita, Monica Try; Zuliani, Rizki; Rini, Candra Puspita (Lembaga Yasin AlSys, 2022)
This research is to determine the Understanding of Science Concepts between students who are given a take and give learning model and students who are given a problem solving learning model. This study uses a quasi experimental methodology. The subject population in this study were all students of class IV SDN Bojongrenged 1 Tangerang Regency consisting of 40 students, class IVA consisting of 20 students as experimental class 1 and class IVB consisting of 20 students as experimental class 2. Data collection techniques in this study using a test instrument. The results of this study are that there are significant differences in the take and give learning model and the problem solving model of understanding concepts in science subjects in SDN Bojongrenged 1 Tangerang Regency. This is evidenced in the results of hypothesis testing conducted in two different classes. The results obtained at posttest of tcount data = 1.091 <ttable = 2.093.